2007
DOI: 10.1136/jcp.2006.044305
|View full text |Cite
|
Sign up to set email alerts
|

Spindle proteins Aurora A and BUB1B, but not Mad2, are aberrantly expressed in dysplastic mucosa of patients with longstanding ulcerative colitis

Abstract: Background: Long term ulcerative colitis (UC) increases the risk of colorectal cancer (CRC). DNA aneuploidy is a common feature of both dysplastic and non-dysplastic colonic epithelia from patients with longstanding UC, and is regarded as an early sign of possible malignant transformation. The spindle proteins Aurora A, BUB1B and Mad2 have been implicated as contributors to aneuploidy and carcinogenesis. Aims: To investigate the role of these spindle proteins in relation to DNA aneuploidy and during the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 42 publications
4
43
0
1
Order By: Relevance
“…Therefore, our results showing that BubR1 elevation is correlated with poor prognosis, cancer aggression, and RFS may reflect the proliferative capacity of tumour cells. It is very likely that the expression of BubR1 is elevated in cycling cells (Burum-Auensen et al, 2007b). Therefore, we speculate that the elevated level of BubR1 coincides with a high mitotic index.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, our results showing that BubR1 elevation is correlated with poor prognosis, cancer aggression, and RFS may reflect the proliferative capacity of tumour cells. It is very likely that the expression of BubR1 is elevated in cycling cells (Burum-Auensen et al, 2007b). Therefore, we speculate that the elevated level of BubR1 coincides with a high mitotic index.…”
Section: Discussionmentioning
confidence: 77%
“…Related to our study, an overexpression of BubR1 has been observed in several human cancers, including breast, gastric, bladder, kidney, and colorectal carcinomas (Myrie et al, 2000;Shichiri et al, 2002;Grabsch et al, 2003;Yamamoto et al, 2007;Pinto et al, 2008). In addition, it has been reported that the overall pattern of BubR1 localisation, revealed by immunostaining, differed between normal and malignant tissues in bladder, colon, pancreas, and skin cancers (Shin et al, 2003;Yamamoto et al, 2007;Burum-Auensen et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…This alteration may occur early in cancer development-it has been reported that Aurora kinase A and Bub1B are overexpressed in preneoplastic mucosa of ulcerative colitis patients. 64 Aberrant expression of proteins that promote mitosis may help ensure that cells do not regard, the results of our compound screen indicate that mitotic regulators may play an important role in helping cancer cells resist death ligands within the inflammatory milieu of a neoplastic lesion. Colon cancer cells have long been noted for altered expression of proteins involved in mitosis.…”
Section: Discussionmentioning
confidence: 91%
“…With regard to colon tissue, Ki67 was found to be highly expressed in the proliferative basal half of the crypt [15]. Also, it has been shown that Ki67 was significantly elevated in ulcerative colitis (UC) colons compared to non-UC control samples, indicating that proliferation is enhanced in UC colonic mucosa [16]. With regard to CRC itself, it has been reported that Ki67 expression correlates with patient age, pathological tumor differentiation, and lymph node involvement [17].…”
Section: Discussionmentioning
confidence: 99%